2020
DOI: 10.1016/j.marpolbul.2020.111691
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microbial plankton diversity as an ecological indicator in the NW Mediterranean coast

Abstract: Research highlights We evaluated microbial pico-and nanoplankton diversity as an ecological indicator in NW Mediterranean coastal waters using metabarcoding of rRNA genes Studied samples were subjected to varying degrees of continental pressures Diversity metrics from microbial eukaryotic communities displayed more suitability to be used as indicators than those of prokaryotes Few microbial planktonic taxa (both from prokaryotes and eukaryotes) showed potential as indicators Implementing fast and simple ecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The stability and resistance in a variable environment under both anthropogenic and climatic pressures may have important implications for management, suggesting that phytoplankton community structure may not be a good indicator of environmental changes 71 , 72 . However, while this study has been focused on regular occurrence patterns and stability signals, possible ‘sentinels’ should probably be looked at in specific phytoplankton attributes, not considered in our analyses, such as diversity and size, or interannual variability and abundance trends of specific taxa.…”
Section: Discussionmentioning
confidence: 99%
“…The stability and resistance in a variable environment under both anthropogenic and climatic pressures may have important implications for management, suggesting that phytoplankton community structure may not be a good indicator of environmental changes 71 , 72 . However, while this study has been focused on regular occurrence patterns and stability signals, possible ‘sentinels’ should probably be looked at in specific phytoplankton attributes, not considered in our analyses, such as diversity and size, or interannual variability and abundance trends of specific taxa.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, alpha diversity analyses showed lower evenness in samples in the vicinity of wastewater outfall, indicating that the relative sequence abundance of species was not evenly distributed, suggesting higher perturbations of bacterial communities. The alpha diversity metric has been previously suggested as a useful tool for assessing anthropogenic impacts on coastal ecosystems and other water bodies ( Cordier et al, 2020 ; Ferrera et al, 2020 ). Studies of freshwater (rivers and lakes) ecosystems report that the vicinity of wastewater sources favors certain microbial groups, leading to biotic homogenization ( Drury et al, 2013 ; Lu and Lu, 2014 ; Saarenheimo et al, 2017 ), whereas a contrasting pattern is reported for polluted marine sediments, with which disturbance promoted co-occurrence of phylogenetically distinct species, resulting in increased diversity ( Galand et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…BBMO is a coastal oligotrophic site in the North-Western Mediterranean Sea (41 • 40′N 2 • 48′E) with not many identi ed natural disturbances and little anthropogenic pressures, with the exception of the construction of a nearby harbor from 2010 to 2012 30,45 . The seasonal cycle is typical for a temperate coastal system 30 , and the main environmental factors in uencing microbial seasonal succession in temperate waters have been well studied and are known 12 .…”
Section: Methodsmentioning
confidence: 99%